A study on suitable habitat for swiftlet farming - Ibrahim, S.H; Teo, W.C; Baharun, A. (Universiti Malaysia Sarawak, (UNIMAS), 2009)
Swiftlet farming is a new industry in Sarawak as compared to other long-standing industries such as rubber, palm oil and timber. IT is one of the businesses that involved a small capital investment that could generate enormous returns in the future. Swiftlet farming involves the conversion of human-centric building into structures for Swiftlet. The purpose of this conversion is to let Siftlet for nesting and protect them.